The Use of Quizzory as a Learning Media to Practice German Grammar for 10th Grade IPS 1 Students at MAN 2 Samarinda - Febrianti, Nani (Universitas Negeri Malang, 2024)
The purpose of this study was to describe the use of Quizzory and describe student’s responses to the use of Quizzory in German subjects for students of class X IPS 1 MAN 2 Samarinda. This study used a qualitative descriptive approach using the instruments of observation sheets and questionnaires. The subjects of this study were students of class X IPS 1 MAN 2 Samarinda, while the German teacher was the observer. The Quizzory consists of multiple-choice questions, cloze test, and sentence rearrangement. Students have difficulties in conjugating irregular verbs. Students stated that Quizzory is a medium that is easy to use and has an attractive appearance and features, and students thought that this media can help them to understand verb conjugation. For the test, students can work on questions in the form of multiple-choice questions better than in the form of cloze test and sentence rearrangement.